Conflict Resolution and The Violation of Religious Freedom: A Narrative from Madura - Abd Hannan (Universitas Islam Negeri (UIN) Mataram, 2023)
This research aims to examine and discuss the violation of freedom of religion or belief in relation to the handling and resolution of internal religious conflicts among Muslims in contemporary Madura. Methodologically, this research is conducted as a qualitative field study. Two types of data, primary and secondary, are utilized for analysis. The sociological perspective on religion and the law of Freedom of Religion or Belief are employed in this study. Through the analysis of field data, it was found that the handling and resolution of internal Muslim conflict cases in Madura reflect certain dynamics. These dynamics include the Sunni-Shia conflict in Sampang, the closure of the Wahhabi Muslim mosque in Pamekasan, and accusations of religious blasphemy against Kiai Fathor. The study also examines the process and practice of resolving internal conflicts among Muslims in Madura.